2014
DOI: 10.1108/mbr-07-2014-0038
|View full text |Cite
|
Sign up to set email alerts
|

Arab and Middle Eastern business research: a review of the empirical literature (1990-2013)

Abstract: Purpose – The purpose of the current study is to examine the empirical research conducted on the Arab region as reported in the top 46 business journals over the past 23 years (1990-2013). After identifying patterns over time (focal country and methodologies), the identified methodological challenges that scholars have reported in their published research are presented. Design/methodology/approach – The Arab region in this study comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Although 1,700 individuals were invited to participate via an email that provided an explanation of the research and a hyperlink to a Survey Monkey website, only 144 questionnaires were returned, for a response rate of 8.47%. Given the experiences of researchers who have previously conducted studies in the region (Ahmad, ; Kalliny & Benmamoun, ), this low response rate was expected. Other studies investigating social media adoption have reported similar response rates (e.g., Ahani, Rahim, & Nilashi, ).…”
Section: Theories On Technology Adoptionmentioning
confidence: 99%
“…Although 1,700 individuals were invited to participate via an email that provided an explanation of the research and a hyperlink to a Survey Monkey website, only 144 questionnaires were returned, for a response rate of 8.47%. Given the experiences of researchers who have previously conducted studies in the region (Ahmad, ; Kalliny & Benmamoun, ), this low response rate was expected. Other studies investigating social media adoption have reported similar response rates (e.g., Ahani, Rahim, & Nilashi, ).…”
Section: Theories On Technology Adoptionmentioning
confidence: 99%
“…The low response rate was expected and assumed to provide an adequate sample based on studies conducted in the region (Lages et al, 2015;Kalliny, and Benmamoun, 2014). "For organizational research, very few organizations [are] willing to allow research [and it is] difficult to obtain permission […]."…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…Additionally, compared to other emerging and developing markets, the Middle East and North Africa (MENA)[1] region has received little attention in the existing international business (IB) literature (Geyikdagi, 1984; Demirbag et al , 2011; Mellahi et al , 2011; Al-Khouri, 2015; Triki and Mayrhofer, 2016). This is mainly attributed to the lack of data availability, as well as to the poor performance of the region in attracting FDI (Jabri et al , 2013; Kalliny and Benmamoun, 2014; Jabri and Brahim, 2015).…”
Section: Introductionmentioning
confidence: 99%